Synthesis of Pyridazinone Derivatives Substituted with Methoxy with Phenyl Hydrazine and In Silico Test of Anticancer Activity - Zulmy, Winda Permata; Sholihah, Putri Mar Atus; Yuda Teruna, Hilwan; Jasril (Universitas Andalas, 2025)
The synthesis of pyridazinone derivatives has gained increasing attention due to their diverse biological activities, particularly as anticancer agents. In this study, novel pyridazinone derivatives substituted with methoxy groups and phenyl hydrazine were synthesized through a multi-step reaction pathway, starting from methoxyacetophenone and glyoxylic acid, followed by cyclization and substitution reactions to yield the target compound 7-(2-methoxyphenyl)-2H-pyridazino[6,1-c][1,2,4]triazine-3(4H)-one. The synthesized compounds were characterized by melting point, TLC, HPLC, UV-Vis, FTIR, NMR, and MS analyses, confirming the expected structures. In silico evaluation was performed using molecular docking against estrogen receptor α (ERα) kinase domain (PDB ID: 1T46), a key protein in breast cancer progression. The docking results showed that the synthesized compounds exhibited strong binding affinities, with compound 8 displaying a binding free energy of –9.1971 kcal/mol and stable interactions with residues Cys673, Leu799, and Phe811. These values were superior compared to the natural ligand and comparable to the reference drug doxorubicin, indicating significant anticancer potential. The results suggest that structural modification of pyridazinone with methoxy and phenyl hydrazine substituents enhances its cytotoxic activity, making it a promising candidate for further development as an anticancer agent.